Hypophosphatemia in Enterally Fed Patients in the Surgical Intensive Care Unit: Common but Unrelated to Timing of Initiation or Aggressiveness of Nutrition Delivery. (April 2017) - Fuentes, Eva; Yeh, D. Dante; Quraishi, Sadeq A.; Johnson, Emily A.; Kaafarani, Haytham; Lee, Jarone; King, David R.; DeMoya, Marc; Fagenholz, Peter; Butler, Kathryn; Chang, Yuchiao; Velmahos, George
Introduction : Hypophosphatemia has been associated with refeeding malnourished patients, but its clinical significance is unclear. We investigated the incidence of refeeding hypophosphatemia (RH) in the surgical intensive care unit (SICU) and its association with early enteral nutrition (EN) administration and clinical outcomes. Methods : We performed a retrospective review of a 2-year database of patients receiving EN in the SICU. RH was defined as a post-EN phosphorus (PHOS) level decrement of >0.5 mg/dL to a nadir <2.0 mg/dL within 8 days from EN initiation. We investigated the risk factors for RH and examined its association with clinical outcomes using multivariable regression analyses. Results : In total, 213 patients comprised our analytic cohort. Eighty-three of 213 (39%) individuals experienced RH and 43 of 130 (33%) of the remaining patients experienced non-RH hypophosphatemia (nadir PHOS level <2.0 mg/dL). Overall, there was a total 59% incidence of hypophosphatemia of any cause (N = 126). Nutrition parameters did not differ between groups; most patients were initiated on EN within 48 hours of SICU admission, and timing of EN initiation was not a significant predictor for the development of RH. The median hospital length of stay (LOS) was 21 and 24 days for those with and without RH, respectively ( P = .79); RH remained a nonsignificant predictor for hospital LOS in the multivariable analysis. Conclusions : RH is common in the SICU but is not related to timing or amount of EN. Hypophosphatemia is also common in the critically ill, but regardless of etiology, it was not found to be a predictor of worse clinical outcomes.